KANDUNGAN PENDIDIKAN AKHLAK DALAM KITAB BIDAYAH AL-HIDAYAH - Suhaimi, Suhaimi (TADRIS: Jurnal Pendidikan Islam, 2015)
Abstract: The effects of globalization causes the problems of science and the cultural values belief that diametrically brings, both positive and negative effects. To avoid the negative effects, it is necessary important to do optimall efforts, which is through moral education that initially introduces ssince childhood. This article describes the moral education existing in the book entittled Bidayah al-Hidayah. The book discusses moral education in complex and integrated way covering teaching of modesty, both  in  human relationships vertically with his God and horizantally with each other.  Keywords: education, moral, Bidayah al-Hidayah